2007
DOI: 10.2141/jpsa.44.161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Leucine on Protein Metabolism of Chicken Embryo Myoblasts is Modulated by Varying Serum Concentrations in the Medium

Abstract: The influence of varying leucine and fetal calf serum (FCS) concentrations in the culture medium on protein synthesis and degradation of chicken embryo myoblasts was examined. Medium+33 contained *, +, ,, / or +*ῌ FCS and ./1 (original concentration of leucine in Medium +33), ,,21 or ./1. mmol leucine/l. Protein synthesis was measured by incorporation of -H-phenylalanine. Protein degradation was measured by release of -H-phenylalanine once incorporated into myoblasts. There was an interaction between leucine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Leucine can directly activate the signaling pathway of mammalian target of rapamycin complex 1 (mTORC1) (Dodd and Tee, 2012). In chickens, we also reported that leucine could stimulate protein synthesis of chicken embryo myoblasts (Oki et al, 2007). Compared to leucine, the information about the influence of other BCAA, isoleucine and valine, on embryo growth of chickens has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Leucine can directly activate the signaling pathway of mammalian target of rapamycin complex 1 (mTORC1) (Dodd and Tee, 2012). In chickens, we also reported that leucine could stimulate protein synthesis of chicken embryo myoblasts (Oki et al, 2007). Compared to leucine, the information about the influence of other BCAA, isoleucine and valine, on embryo growth of chickens has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Leucine can also directly activate the signaling pathway of mammalian target of rapamycin complex 1 (mTORC1) (Dodd and Tee, 2012). In chickens, we reported that leucine could increase protein synthesis of chicken embryo myoblasts as well as mammals (Oki et al, 2007). Compared to leucine, however, the information about valine, which is also one of branched amino acids, on protein synthesis of chicken embryo myoblasts has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…In chickens, we have already reported that leucine could stimulate protein synthesis of chicken embryo myoblasts (Oki et al, 2007). Compared to leucine, the information about the influence of valine, which is also one of branched amino acids, on protein synthesis of chicken embryo myoblasts has been limited.…”
Section: Introductionmentioning
confidence: 99%